Arte e ação em Alberti - Patricia Gomes de Azevedo (2005)
This study has as its object the work of Leon Battista Alberti, an Italian humanist who lived in century XV, and considered by some as one of the pioneers authors to systematize, in his treadses, the art in the modern era. The intention is to establish the relation between art and action in his thoughts through the reading two of his texts: De Pictura e I Libri DellaFamiglia, where the analysis will focus on how the author builds his reflection about art, founding it in science and ethics, and valuing art not only by its connection with beaut)' but else binding art to the history the one that figures and represents itself and mainly that one concerned to educate the citizens. In this horizon, the concepts of action and historyappear as the major elements to articulate the Albertian thought and the perspective, spatial or temporal, which projected in life and in painting will serve as tool to illustrate Alberti's forma mentis. The aim is show, in Alberti, the art is not ncit/ira, but action. In the same sense asthe virtue, the art is a construction that solved in "real" reaches the soul and changes the world, combating against a narcissist life st}'le towards building a happier world.